2022
DOI: 10.1159/000522247
|View full text |Cite
|
Sign up to set email alerts
|

The Role of <b><i>Faecalibacterium, Roseburia</i></b>, and Butyrate in Inflammatory Bowel Disease

Abstract: Faecalibacterium and Roseburia are major producers of butyrate in the intestine. A reduced abundance of the organisms and a concurrent reduction in butyrate levels are associated with inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
1
18
1
Order By: Relevance
“…Moreover, we found that the levels of lipid, Alb and Hb were positively correlated with the abundances of SCFA-producing probiotics which enriched in HCs, such as Lachnospiraceae_ND3007_group , Faecalibacterium , Roseburia , Dorea and Butyricicoccus ( Figure 3 ), indicating the enrichment of probiotics were related to the healthy physiological state of the host. Faecalibacterium and Roseburia are major producers of butyrate, which decreased Mtb -induced inflammation as well as insulin resistance ( Jo et al., 2021 ; Faden, 2022 ). Meanwhile, the mentioned indexes were negatively correlated with the abundances of Lactobacillus , Erysipelatoclostridium and Sellimonas , which enriched in PTB patients ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that the levels of lipid, Alb and Hb were positively correlated with the abundances of SCFA-producing probiotics which enriched in HCs, such as Lachnospiraceae_ND3007_group , Faecalibacterium , Roseburia , Dorea and Butyricicoccus ( Figure 3 ), indicating the enrichment of probiotics were related to the healthy physiological state of the host. Faecalibacterium and Roseburia are major producers of butyrate, which decreased Mtb -induced inflammation as well as insulin resistance ( Jo et al., 2021 ; Faden, 2022 ). Meanwhile, the mentioned indexes were negatively correlated with the abundances of Lactobacillus , Erysipelatoclostridium and Sellimonas , which enriched in PTB patients ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…80 Other microorganisms have the ability to produce butyrate, which can not only alleviate inflammation but also encourage the production of hormones for a healthy metabolism. 81 According to the decrease in the abundance of Firmicutes in group M, it was indicated that acetic acid destroyed the oral epithelial barrier, damaged the beneficial metabolism of microbes, and led to an imbalance in oral microecology. After being treated with LTE, the relative abundance of Firmicutes and Actinobacteria increased significantly, while that of Proteobacteria decreased (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Algiphilus can produce succinic acid and a small amount of acetic and propionic acids, and that succinic acid can activate intestinal gluconeogenesis, imparting beneficial effects on blood sugar metabolism and obesity management [ 53 ]. The genus Faecalibacterium is one of the most important bacteria in the human gut flora and one of the important producers of butyric acid, which has anti-inflammatory and protective effects on the digestive system from intestinal pathogens, particularly effective in obese patients [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%